Delirium screening in a stroke unit by nurses using 4AT: Results from a quality improvement project - Håkon Ihle‐Hansen; Nina Johnsen; Tatiana Jankowiak; Guri Hagberg; Marte M. Walle‐Hansen; Ida Landgraff; Gunnhild Høvik; Else Graven; Marius Myrstad (Wiley, 2023)
Abstract Aim To assess the feasibility of delirium screening with the screening tool 4AT conducted by stroke unit nurses. Design Observational. Methods Patients with confirmed acute stroke admitted to the stroke unit at Bærum Hospital, Norway, from March to October 2020, were consecutively recruited. Nurses performed delirium screening using the rapid screening tool 4AT within 24 h of admission, at discharge and when delirium was suspected, and filled out a questionnaire assessing their experiences with the delirium screening. A geriatrician validated the delirium diagnosis. Results In all, 62 patients were included, mean age 73.3 years. 4AT was performed according to protocol in 49 (79.0%) and 39 (62.9%) patients at admission and discharge respectively. Lack of time (40%) was reported as the most common reason for not performing delirium screening. The nurses reported that the felt competent to carry out the 4AT screening, and did not experience it as significant extra workload. Five patients (8%) were diagnosed with delirium. Delirium screening performed by stroke unit nurses seemed feasible and the nurses experienced that 4AT was a useful tool for this purpose.